[The Rationality of Official Intervention in the Forward Exchange Market]: Reply - Stein, Jerome L. (Quarterly Journal of Economics, 1965)
The Rationality of Official Intervention in the Forward Exchange Market: Reply Get access Jerome L. Stein Jerome L. Stein Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 1, February 1965, Pages 150–152, https://doi.org/10.2307/1880520 Published: 01 February 1965